CONSUMER FACTORS IN DECIDING TO PURCHASE ONLINE AT SHOPEE E-COMMERCE DURING THE COVID-19 PANDEMIC - Syahrul Amsari; Dian Permata Sari (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the causes of consumer behavior as well as to determine the form of consumer behavior in deciding online purchases at e- commerce shopee during the covid-19 pandemic. The approach used in this study is a qualitative approach. The data analysis technique used is through data collection and process interview, data reduction, and drawing conclusions.The results show that there are two factors that cause consumer behavior in deciding to purchase online at e-commerce shopee during the covid- 19 pandemic, namely external factors and internal factors. Where the external factors are in the form of the implementation of the PSBB system (Social distancing, orders at home, prohibitions not to gather) and internal factors in the form of encouragement from within the respondents themselves, especially among students of the Sharia Business Management Study program, Faculty of Islamic Religion UMSU. Furthermore, there is a factor of convenience and respondents' trust, the existence of extra free shipping, discounts, 12.12 sales, so that it leads to online purchasing decisions on e-commerce shopee.The form of consumer behavior in deciding to purchase online at e- commerce shopee during the covid-19 pandemic by the respondents can be seen in terms of the form of product shopping behavior carried out such as shopping for health products such as masks, vitamin C, hand sanitizers and 35% others. followed by snack products etc.Keywords: Consumer Behavior, Online Purchase, Shopee E-commerce, Covid- 19